Urinary incontinence and risk factors among Croatian female athletes - a pilot cross-sectional observational study - Kelecic, I. L.; Schuster, S.; Ursej, E. (Physical Activity Review, 2023)
Urinary incontinence (UI) in female athletes (FA) is a globally concerning but neglected topic in Croatia. The purpose was to examine the occurrence and severity of UI in Croatian FA and occurrence-associated factors. Methods: In May 2022, an anonymous online survey collecting general sports characteristics and the Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF) were sent to individual FA. Obtained data were analysed with the PSPP program: chi-square test, t-test and analysis of variance with a defined significance level of p < 0.05. Results: The presence of UI in the total sample of 70 FA competing in 12 different sports is 24.3 %: 8 (29.6 %) handball players, 3 (42.9 %) tennis players, 2 (40 %) water polo players, one (14.3 %) synchronised swimmer, seven soccer players (14.3 %), one weightlifter (50 %) and the only swimmer (100 %). According to ICIQ-UI SF, in 70.59 % of FA with UI, a small amount of urine leaks approximately once a week or less often, mainly after urination and dressing up (35.29 %). The UI interference with quality of life is mild (70.59 %) and moderately severe (29.41 %), and the UI severity is slight (47 %) to moderate (53 %). Smokers report UI to a greater extent (X2(1, n = 70) = 4.666, p < 0.05), while other sports and FA characteristics did not yield significant findings. Conclusions: UI is present in a quarter of examined Croatian FA, with mild to moderate severity. It mildly interferes with the quality of life and seems to be associated with smoking. Our findings contribute to preserving women's health in sports and apply to UI assessment in FA and counselling on smoking cessation as a proven UI risk.